Evidence-Based Treatment of Pseudomonas aeruginosa Infections: A Critical Reappraisal - Arta Karruli; Christian Catalini; Chiara D'Amore; Francesco Foglia; Fabio Mari; Arjan Harxhi; Massimiliano Galdiero; Emanuele Durante-Mangoni (MDPI AG, 2023)
Multidrug-resistant (MDR)/extensively drug-resistant (XDR) Pseudomonas aeruginosa is emerging as a major threat related to adverse patient outcomes. The goal of this review is to describe evidence-based empiric and targeted treatment regimens that can be exploited when dealing with suspected or confirmed infections due to MDR/XDR P. aeruginosa. P. aeruginosa has inherent resistance to many drug classes, the capacity to form biofilms, and most importantly, the ability to quickly acquire resistance to ongoing treatments. Based on the presence of risk factors for MDR/XDR infections and local epidemiology, where large proportions of strains are resistant to classic beta-lactams, the recommended empirical treatment for suspected P. aeruginosa infections is based on ceftolozane-tazobactam or ceftazidime-avibactam. Where local epidemiology indicates low rates of MDR/XDR and there are no risk factors, a third or fourth generation cephalosporin can be used in the context of a "carbapenem-sparing" strategy. Whenever feasible, antibiotic de-escalation is recommended after antimicrobial susceptibility tests suggest that it is appropriate, and de-escalation is based on different resistance mechanisms. Cefiderocol and imipenem-cilastatin-relebactam withstand most resistance mechanisms and may remain active in cases with resistance to other new antibiotics. Confronting the growing threat of MDR/XDR P. aeruginosa, treatment choices should be wise, sparing newer antibiotics when dealing with a suspected/confirmed susceptible P. aeruginosa strain and choosing the right option for MDR/XDR P. aeruginosa based on specific types and resistance mechanisms.